BITUN, Ricardo. Mochileiros da Fé. 2. ed. São Paulo: Editora Reflexão, 2011. 129p. - Espírito Santo, Magno Lessa do (Vox Scripturae - Revista Teológica Internacional, 2015)
BITUN, Ricardo. Mochileiros da Fé. 2. ed. São Paulo: Editora Reflexão, 2011. 129p.